2022
DOI: 10.3390/polym14153114
|View full text |Cite
|
Sign up to set email alerts
|

An Effective Shrinkage Control Method for Tooth Profile Accuracy Improvement of Micro-Injection-Molded Small-Module Plastic Gears

Abstract: An effective method to control the non-linear shrinkage of micro-injection molded small-module plastic gears by combining multi-objective optimization with Moldflow simulation is proposed. The accuracy of the simulation model was verified in a micro-injection molding experiment using reference process parameters. The maximum shrinkage (Y1), volume shrinkage (Y2), addendum diameter shrinkage (Y3), and root circle diameter shrinkage (Y4) were utilized as optimization objectives to characterize the non-linear shr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Studies showed that the use of the microinjection method for PDO processing makes it possible to obtain samples with high uniformity and shape stability [164]. The technique was also proven excellent in the high-precision and high-performance fabrication of small-module plastic gears [165]. Subsequently, Lin et al used µIM to fabricate light guiding plates (LGPs) as parts of liquid crystal displays [166].…”
Section: Microinjection Moldingmentioning
confidence: 99%
“…Studies showed that the use of the microinjection method for PDO processing makes it possible to obtain samples with high uniformity and shape stability [164]. The technique was also proven excellent in the high-precision and high-performance fabrication of small-module plastic gears [165]. Subsequently, Lin et al used µIM to fabricate light guiding plates (LGPs) as parts of liquid crystal displays [166].…”
Section: Microinjection Moldingmentioning
confidence: 99%
“…Optimization methods have evolved over the years. This development has moved from the trial and error method through the development of analytical calculations to the use of statistical models and the use of more advanced techniques such as second-order mathematical models and the use of artificial intelligence [ 16 , 17 , 18 , 19 ]. These models consider using existing plant equipment or specialized Engineering Add Computer (CAE) software such as Moldflow ® [ 20 ].…”
Section: Theoretical Considerations On Injection Molding Process Opti...mentioning
confidence: 99%
“…The results showed that the air gasification process yields 42.68% and 89.58% hydrogen and energy efficiencies at optimum conditions, respectively, while these values were higher for steam gasification, i.e., 64.02% for hydrogen and 96.52% for energy efficiency [14]. Similarly, other researchers used RSM to optimize printing parameters of sintered 316 L stainless steel [15], manufacturing of small-module plastic gears [16], a system based on biomass-fueled solid oxide fuel cell [17], solid polymer electrolyte-based technique for the electrochemical treatment of wastewater [18], and decolorization of congo red solution using iron-doped zinc oxide nanoparticles [19].…”
Section: Introductionmentioning
confidence: 96%